Neutrophil function in the healing wound: adding insult to injury? - Dovi, Julia V.; Szpaderska, Anna M.; DiPietro, Luisa A. (Thrombosis and Haemostasis, 2004)
Cells of the innate immune system, including neutrophils and macrophages, are a highly visible component of normal wound healing in adult mammals. The role of inflammatory cells in the healing wound has been widely investigated, and evidence for both positive and negative influences exists. Several recent investigations support the emerging paradigm that robust inflammation is detrimental to wound closure. This developing information suggests that the functional role of inflammatory cells in wound healing must be reevaluated.
Keywords: Wound healing; neutrophils; macrophages; inflammation